PENGGUNAAN MEDIA FLASHCARD DALAM MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI - Budiyanto, Cepi; Hotimah, Empit (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2022)
This research aims to determine the design, learning process and improvement of descriptive writing skills using flashcard media in Indonesian subjects in the second grade SDIT PERSIS 99 Rancabango. The benefit of this research is to identify and apply a learning media that can improve and train students' description writing skills properly and correctly in the second grade SDIT PERSIS 99 Rancabango. The research design was Classroom Action Research (PTK) using the Kemmis & Mc Taggar model. The subjects were students of the second grade SDIT PERSIS 99 Rancabango. The data collection methods were tests, observation and documentation. Data analysis techniques are quantitative data obtained from test results and qualitative data from observations.The results showed that the writing skills of the second grade students of SDIT PERSIS 99 Rancabango improved by using flashcard media. This increase is evidenced by the results of observations and the average value of descriptive writing skills. The results of the observations showed that students were more enthusiastic in participating in learning. The mean score of students also increased from 62.68 in the pre-action to 74.39 in the first cycle and 82.32 in the second cycle. The percentage of students who have reached the KKM writing skills also increased from 50% in pre-action to 71% in the first cycle and 93% in the second cycle